Social Media and Unprofessional Pharmacist Conduct: A Cross-Sectional Survey of Boards of Pharmacy - Jessica Skelley; Peter Hughes; Lindsey Elmore (University of Minnesota Libraries Publishing, 2013)
Purpose: To determine how often boards of pharmacy (BOPs) receive complaints related to licensee's online behavior, and what types online behaviors may prompt an investigation of a licensee. Methods: A survey (consisting of questions related to BOP's management of complaints against licensee online behavior and 10 case vignettes) was adapted from a previous survey of United States medical boards. Vignettes encompassed themes such as patient confidentiality, derogatory language, alcohol use, false or misleading product claims, and others. Following institutional review board approval, survey materials were distributed via email by the National Association of Boards of Pharmacy to 63 domestic and international boards of pharmacy. Completed surveys were analyzed using descriptive statistics. The proportion of respondents who indicated that the vignette would "very likely" or "likely" result in an investigation was used to determine consensus. Proportions of >75%, 50%-75% and <50% were classified as high, moderate and low consensus, respectively. Results: Fourteen completed surveys (22.2%) were received. Sixty percent of respondents stated that their board has been involved in managing a complaint regarding the online behavior of a licensee, and that disciplinary actions including revocation or suspension of license, letter of reprimand, and monetary fines have been enacted. While 79% of responding BOPs have a policy regarding Internet usage, 36% are unsure whether the policies are sufficient to cover online professionalism. One vignette, where a pharmacist made misleading claims regarding a compounded product, achieved high consensus for likelihood to prompt an investigation. Moderate consensus was achieved for a breach of patient confidentiality, inappropriate alcohol use, and misrepresentation of professional credentials. Conclusion: Boards of pharmacy are widely varied in what types of online behaviors may prompt an investigation. Additional dialogue is needed among pharmacy leaders to determine best practices.   Type: Original Research